Entrerprise Architecture dengan Togaf ADM untuk Optimalisasi Alur Kerja Digital Agency Skala Kecil - Nasrullah Gunawan; Cindy Anggriani; Dzakwan Abbas; Muhammad Faruqi Adri; Much Nur Syams Simaja; Wilona Ramadhani K.; Sherly Pitaloka; Ika Yusnita Sari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Boutique Boutique digital agencies frequently encounter operational bottlenecks caused by disjointed workflows and reliance on manual data handling. Using Agency XYZ as a case study, this research identifies critical issues such as asset-caption mismatches and data security vulnerabilities arising from unmanaged 'Bring Your Own Device' (BYOD) practices. To address these challenges, this study applies the TOGAF Architecture Development Method (ADM) to design a comprehensive Enterprise Architecture tailored for small organizations. The resulting solution presents a blueprint for a centralized, web-based information system that seamlessly integrates with existing Google Workspace infrastructure and WhatsApp notifications. Key contributions of this design include an automated 'auto-switch' task delegation mechanism to prevent bottlenecks and a unified data model that establishes a Single Source of Truth (SSOT). The proposed architecture is projected to significantly reduce coordination latency, mitigate human error, and establish a secure, scalable operational framework for small creative teams.